ÎN BALANŢA LIBERTĂŢII: RECUNOAŞTEREA POSTBELICĂ A CREŞTINILOR DUPĂ EVANGHELIE DIN ROMÂNIA (1946-1950) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
The balance of Freedom: Public Postbellum Recognition of the Romanian Brethren believers (1946-1950).The public recognition of the Romanian Brethren Assemblies as being an  official Cult rested in the balance of freedom. As an historic arch over time,  both recognitions took place under two Governments lead by the same man,  Petru Groza, in the time of two very different postbellum regimes. The first  recognition was approved by a pro communism Government, in the last years  of the Monarchy, where there existed some forms of liberty, whereas the second one was by a completely and eminently Communist Government in the beginning of the Romanian Stalinism, supervised by a careful control of  the State. The analysis of the two official documents, in the background of the  years that were issued in, offer an interesting perspective over the  Religious freedom from the point of view of one Denomination that has been  through the process of the institutional recognition, twice in just a period of  four years.